Resilient telecommunication network design knowledge / Mohd Idhamm Ibrahim - Ibrahim, Mohd Idhamm (2016)
Telecommunication industry has growing fast recently. Telecommunication network become important for communication not only for business but also for the many lifestyle and some critical communication services such as government defense, banking sectors and transportation control. Ensuring the communication network to stay up all the time is not an easy task to the network designers. In telecommunication industry, employee attrition is very high and unmanageable where demand of network designer is very high from others organizations and competitors. Every year, organization experiencing staff retirement, transferred and resignation which they take away the valuable network design knowledge with them. Network design knowledge is an abstract and scattered around the organization and individual designers due to network design is a project based task and the requirement from customer with another customer is different makes the knowledge captured are often kept in silos. This research has discovers three types of knowledge which is Telecommunication Network Resilient Definitions, Resilient Network Design Knowledge and Resilient Network Design Process Knowledge. In the end of findings, author proposed a process model in designing resilient telecommunication network and a guideline for future reference. The knowledge captured through expert's interview, documents analysis and observation where author directly involved in designing resilient telecommunication network. Therefore, in the taxonomy development, the concept and relationship are derived from customer requirements and the technologies used to fulfill the customer needs. Taxonomy approach was utilized to classify the telecommunication technologies and group for easy understanding. The significance of the research is about exploring the telecommunication network design processes and modelled the processes into structured ways for future reference. Organization can use this resilient telecommunication network design process model as guidance to inexperience and young designers to design the network and propose the best solution to the customers. The findings discovered in the network design activities, intensified knowledge happened in the interpreting customer requirements phase. During this phase, lots of tacit and explicit knowledge created and embedded in the solutions to the customer requirements.